The MobileMaker: an experiment with a Mobile Makerspace by Dana Gierdowski and Dan Reis. Issue 4 (16th November 2015) - Gierdowski, Dana; Reis, Daniel
Abstract : Purpose: – The purpose of this paper is to discuss the design, implementation, and pilot of a Mobile Makerspace at a private, southeastern liberal arts institution that did not have a campus-wide makerspace. In an effort to give students in a residential hall access to maker tools and technologies and also meet the needs of a campus-wide writing initiative, a team of administrators and staff worked to build and design programing for the "MobileMaker, " a pop-up Mobile Makerspace. Design/methodology/approach: – The authors explain how the equipment was chosen based on a variety of user skill levels. The technical specifications of the MobileMaker are also detailed, which includes 3D printing and crafting tools, and a variety of electronics. In addition, they explain how a mobile cart was modified to house and secure the equipment so it could be stored in an unsecured area. The team experienced several challenges with the MobileMaker project, including the overall durability of the mobile cart and the lack of a dedicated staff to manage the equipment. Findings: – The authors conclude that mobility and security were mutually exclusive with the mobile design that was chosen. Greater mobility was sacrificed to achieve greater security via locked doors and compartments that added weight to the cart. While the goal of increased student access to maker tools and technologies was met, the level of access was often limited due to staffing limitations. Originality/value: – An unanticipated outcome of the project was the conversations that were generated about the need and demand for a dedicated makerspace open to the entire campus community.